Impacto de la Paratuberculosis bovina en la productividad de ganaderías en el Ecuador - Arévalo Santana, Nayely Ayli (2024)
In the development of this research based on the "Impact of bovine paratuberculosis on the productivity of livestock in Ecuador." in which it was proposed as an objective, to evaluate the impact of bovine paratuberculosis on the productivity of livestock in Ecuador. The methodology, it is determined that it was based on a basic type of research, where it was developed under a descriptive-analytical approach, with a qualitative research design, in its development the general production of cattle in Ecuador, paratuberculosis, definition, causal agent, its life cycle, its symptoms, its damages caused to cattle, its economic impact on the different types of livestock within Ecuador, global and regional prevalence, infection mechanisms and development of the disease, vacations and eradication programs were determined. In terms of the results, the impact of paratuberculosis in livestock in Ecuador is evident at 25% of the infection rates in cattle, because its early detection is complicated without the respective ELISA or PCR tests. In conclusion, the economic losses associated with bovine paratuberculosis are significant, with estimates ranging from $200 to $500 per infected animal, due to reduced milk production and body weight. The epidemiology of bovine paratuberculosis in livestock in Ecuador has a variable prevalence, factors such as high livestock intensity and inadequate management practices increase the mortality rate of Mycobacterium avium transmission.